Chemistry and Biochemistry of Winemaking, Wine Stabilization and Aging 2021
DOI: 10.5772/intechopen.93529
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Technology of Wine Aging with Oak Chips

Abstract: The use of wood chips is a common winemaking practice that has been permitted in Europe since the early 2000s. The use of oak chips, or other wood alternative products, has not always been favorably viewed by both producers and wine consumers. Beyond possible misuse, however, wood chips are a useful tool for the optimal achievement of numerous oenological objectives, including the extraction of certain volatile odor compounds from oak wood chips as well as compounds that will improve wine quality. This chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The use of wood chips or old barrel fragments with different toasting levels has also been investigated as an alternative to ageing in wooden barrels. It has been shown that wooden chips could be used for short-aged wines and to reuse wood from old barrels, but new wooden barrels result in more complex aromas and higher wine quality [ 32 ], although several other factors must also be taken into account, such as the toasting level, wine type, wood type, barrel age, contact surface between wood and wine and other [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of wood chips or old barrel fragments with different toasting levels has also been investigated as an alternative to ageing in wooden barrels. It has been shown that wooden chips could be used for short-aged wines and to reuse wood from old barrels, but new wooden barrels result in more complex aromas and higher wine quality [ 32 ], although several other factors must also be taken into account, such as the toasting level, wine type, wood type, barrel age, contact surface between wood and wine and other [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of wood fragments (chips) for the ageing of wines, distillates and vinegars is a widespread practice within the European Union and complies with specific regulations to defend the Protected Geographical Indication (PGI) from possible fraud. Their use, when authorized, is intended to reduce production time and costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other compounds can be found in oak-aged distillates. Some of them may derive from the Maillard reaction, which occurs during the wood-toasting phase and leads to the formation of coloured compounds (melanoidins) and several aromas with a high olfactory impact, such as pyrazines and furan derivatives [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations